2019
DOI: 10.1002/hrm.21997
|View full text |Cite
|
Sign up to set email alerts
|

Development or maintenance? Dual‐oriented human resource system, employee achievement motivation, and work well‐being

Abstract: Drawing on the person–organization fit theory, this study elaborates a dual‐oriented human resource (HR) system and explores when and how two HR bundles (development vs. maintenance) influence work well‐being. The results of the confirmatory factor analysis with a sample of 1,946 supervisors from a Chinese high‐tech firm show that the dual‐oriented HR model fits the data better than a holistic HR system. In another study with a multilevel sample of 64 corporate branches and 434 employees, the findings confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 96 publications
1
28
0
1
Order By: Relevance
“…We asked supervisors to rate team-level EORs, as they have knowledge on the content and extent of the inducements that their organizations offer to teams as well as the contributions that their organizations expect from teams by interpreting, transferring, and implementing firm HRM practices. This procedure has also been used in recent studies to measure team-or department-level HRM practices (Van De Voorde and Beijer, 2015;Lin et al, 2019). First, we asked the supervisors to indicate the job titles and number of members in the teams and provide a brief job description before rating the OI and EC of the teams so that they can keep the entire team in mind.…”
Section: Measures Eorsmentioning
confidence: 99%
“…We asked supervisors to rate team-level EORs, as they have knowledge on the content and extent of the inducements that their organizations offer to teams as well as the contributions that their organizations expect from teams by interpreting, transferring, and implementing firm HRM practices. This procedure has also been used in recent studies to measure team-or department-level HRM practices (Van De Voorde and Beijer, 2015;Lin et al, 2019). First, we asked the supervisors to indicate the job titles and number of members in the teams and provide a brief job description before rating the OI and EC of the teams so that they can keep the entire team in mind.…”
Section: Measures Eorsmentioning
confidence: 99%
“…Some studies have demonstrated that HRM systems are positively related to work well-being (e.g. Fan et al, 2014;Huang et al, 2016), whereas others have shown that their association with work well-being varies by types of HRM practices (Lin et al, 2020;Korff et al, 2017;Wood and de Menezes, 2011). Several scholars have even described HRM system as a double-edged sword, boosting organizational performance at the expense of employees' job stress and dissatisfaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Halbesleben and Bowler (2007) showed that various components of achievement motivation mediate the relationship between job performance and emotional exhaustion. Lin., Li, and Lam (2019) found that development-oriented HR practices are more positively related to work well-being when individual achievement motivation is high. The results guide the effective design of HR practices.…”
Section: Achievement Motivationmentioning
confidence: 99%